GRAPHICS OF COVERS OF ODESSA SATIRICAL PERIODICALS OF THE END OF XIX – THE BEGINNING OF XX CENTURY - Михалевич, В. В. (Art and Design, 2020)
Purpose. Investigate the features of the design of covers and pages of satirical publications in Odessa in the late XIX – early XX century. Identify the development and general features of the design of satirical periodicals of Odessa in the late XIX – early XX centuries. Methodology. The research methodology is based on comparative and historical methods that help to trace the relevant retrospective of the development of satirical periodicals. Applied art analysis allows to explore, identify, compare and describe the features of the design of certain publications. Results. On the basis of examples and the processed literary sources graphic-stylistic and technical features of artistic design of covers and pages of satirical periodicals of Odessa in the late XIX – early XX centuries are defined. The design of covers of such magazines as «Pchelka», «Crocodil», «Bomba» is analyzed. It was found that the considered editions did not follow a single style of graphic material, but this did not interfere with the overall design. Most satirical magazines had a symmetrical hierarchical cover composition with a limited polychrome palette. The development of humorous and satirical publications from simple leaflets with caricatures to magazines with high-quality art design is traced. The semantic load of the visual material of the analyzed satirical editions is determined. Scientific novelty. The general features of artistic design of covers and pages of satirical editions of Odessa of the end of XIX – the beginning of XX century are defined. Practical significance. The given data concerning the design of covers and pages of satirical magazines of Odessa of the end of XIX – the beginning of XX century will help in understanding of traditions of the Ukrainian graphic design.